Penilaian risiko pada layanan pembayaran pensiun PT Asabri Bandung: Sebuah praktek terbaik untuk penguatan tata kelola perusahaan - Taufik, Nur Imam; Sulistianti, Intan; Pradesa, Hafid Aditya (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The pension payment service is one of the important services carried out by PT Asabri, a BUMN that is trusted to manage pension funds for employees within the TNI and POLRI in Indonesia. Because every company does not want to suffer losses so it decides to manage risk properly. The purpose of this study is (1) to find out the risks that have the potential to arise in the pension payment service at PT Asabri Branch Bandung, (2) to explain the results of the risk assessment in the pension payment service based on the ISO 31000:2018 frame of reference. This research method includes qualitative research, using focus group discussions and document review as data collection techniques. From this study, six potential risks emerged, with one risk being at a moderately high level and five other risks including being at a moderately low level. The risk that needs more attention is the risk that the disbursement of funeral expense claims is received by the wrong person. The formulation of actions as risk mitigation that has been assessed has been presented in this article, along with practical recommendations for improving the application of Risk Management at PT Asabri Bandung.